2019
DOI: 10.1177/0300060518818300
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning ameliorates indirect acute lung injury by modulating phosphorylation of IκBα in mice

Abstract: Objective Acute lung injury is responsible for mortality in seriously ill patients. Previous studies have shown that systemic inflammation is attenuated by remote ischemic preconditioning (RIPC) via reducing nuclear factor-kappa B (NF-κB). Therefore, we investigated whether lipopolysaccharide (LPS)-induced indirect acute lung injury (ALI) can be protected by RIPC. Methods RIPC was accomplished by 10 minutes of occlusion using a tourniquet on the right hind limb of mice, followed by 10 minutes of reperfusion. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…An LPS-induced ALI mouse model was used in the present study, as its reliability and reproducibility have been previously confirmed ( 42 ). The results of the examination of the lung exudate, H&E staining and cell counting in the BALF identified that both CM and F-CM significantly prevented LPS-induced lung injury in mice, and the effects of F-CM treatment were superior.…”
Section: Discussionmentioning
confidence: 79%
“…An LPS-induced ALI mouse model was used in the present study, as its reliability and reproducibility have been previously confirmed ( 42 ). The results of the examination of the lung exudate, H&E staining and cell counting in the BALF identified that both CM and F-CM significantly prevented LPS-induced lung injury in mice, and the effects of F-CM treatment were superior.…”
Section: Discussionmentioning
confidence: 79%
“…NLRP3 inflammasome activation results in caspase mediated cell death [ 119 ]. Several studies haves demonstrated that RIC modulates NF-κB activity via in both ischaemia and endotoxaemia [ 74 , 76 , 92 , 117 , 130 ]. TLR4 Toll-like receptor 4, DAMPS damage associated molecular patterns, HMGB1 high mobility group box 1, TNF-α tumour necrosis factor alpha, LPS lipopolysaccharide, RAGE Receptor for advanced glycation end-products, ERK extracellular signal related kinase, MAPK mitogen activated protein kinase, EGR-1 early growth response 1, TAK1 transforming factor-β-activated kinase 1, Iκβ inhibitor kappa beta kinase, NF-κβ nuclear factor kappa beta …”
Section: The Inflammatory Hypothesis Of Organ Protectionmentioning
confidence: 99%
“…RIC reduces inflammatory cytokine levels and improves survival in rodent models of lipopolysaccharide (LPS) induced endotoxaemia [ 68 , 74 , 76 ]. In mice receiving three cycles of hind limb I/R (10 min ischaemia/10 min reperfusion) prior to LPS exposure, there was a significant survival benefit from RIC (10% of the control group survived vs 60% of the intervention group; p < 0.001 ).…”
Section: Cytokines In Myocardial Infarction and Infectionmentioning
confidence: 99%
See 2 more Smart Citations